Pengembangan Mitra Keuangan Dan Kopersi Pada Masyarakat Negeri Suli Kecamatan Salahutu Kabupaten Maluku Tengah - Frederik Willem Ayal; Erdyd S Bakarbessy; Eva Tirza Mayaut; Eunike Auparay; Natanyel Y. Rerung; Ivander M Metubun; Eva Latuhukum; Fally Tuhenay; Egan Ray Sahetapy; Shara Venesia Ubra; Melvin lopulalan; Lumas Patrisia Welerubun; Marthafina Fordatkosu; Elizabeth Tapilaha; Getsefyor Hans de Fretes; Meike Handayani Kunu; Martha wuritimur; Haris Degres Rahayaan; Marklen Manaha; Anderson Siwalette (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
KKN (Real Work Lecture) is a community service activity program carried out by students with a cross-scientific and sectoral approach at certain times and regions in Indonesia. Suli is one of the states in Salahutu District, Central Maluku Regency, Maluku Province. KKN students who have been placed in this location must mingle, adapt to the community and are required to create work programs obtained from observations in the community. The results of observations obtained in Suli are problems that must be turned into work programs to be carried out as KKN students. The work program which is the flagship program is Socialization of Financial Partners and Cooperatives (Empowerment of High School Children in Financial Education and Introduction to Cooperatives). Writing articles using the Socialization and TPA (Primary Knowledge Test) methods